PENGELOLAAN PEMERINTAHAN DESA PERSPEKTIF SIYASAH SYAR’IYYAH : Studi Desa Manimbahoi Kecamatan Parigi Kabupaten Gowa - Rismayanti, Rismayanti; Jafar, Usman; Halimang, St. (Prodi Hukum Tata Negara (Siyasah Syariyyah) Fakultas Syariah dan Hukum UIN Alauddin Makassar, 2023)
This study aims to find out how the government management system in Manimbahoi Village, Parigi District, Gowa District, shar'iyyah siyasah perspective. This type of research is field research using normative juridical and theological approaches. The results of this study show that the concept of government management in Manimbahoi Village, Parigi District, Gowa Regency is based on Law Number 6 of 2014 concerning Villages which includes planning, community empowerment, organizing village government institutions, using village resources, and supervising village governance. The concept of shar'iyyah siyasah emphasizes the administration of government, including the village government level held to achieve welfare - benefit in various aspects of life, if this principle becomes a benchmark, then obedience to ulil amri will follow the command to obey Allah and His Messenger.